Salivary Cortisol Levels and Depressive Symptomatology in Consumers and Nonconsumers of Self-Help Books: A Pilot Study - Catherine Raymond; Marie-France Marin; Anne Hand; Shireen Sindi; Robert-Paul Juster; Sonia J. Lupien (Neural Plasticity)
The self-help industry generates billions of dollars yearly in North America. Despite the popularity of this movement, there has been surprisingly little research assessing the characteristics of self-help books consumers, and whether this consumption is associated with physiological and/or psychological markers of stress. The goal of this pilot study was to perform the first psychoneuroendocrine analysis of consumers of self-help books in comparison to nonconsumers. We tested diurnal and reactive salivary cortisol levels, personality, and depressive symptoms in 32 consumers and nonconsumers of self-help books. In an explorative secondary analysis, we also split consumers of self-help books as a function of their preference for problem-focused versus growth-oriented self-help books. The results showed that while consumers of growth-oriented self-help books presented increased cortisol reactivity to a psychosocial stressor compared to other groups, consumers of problem-focused self-help books presented higher depressive symptomatology. The results of this pilot study show that consumers with preference for either problem-focused or growth-oriented self-help books present different physiological and psychological markers of stress when compared to nonconsumers of self-help books. This preliminary study underlines the need for additional research on this issue in order to determine the impact the self-help book industry may have on consumers’ stress.